(untitled) (Dhaka University Law Journal, 2023)
The doctrine of restraint is no more confined to the entrenched words of the sections of the Contract Act, 1872. It has travelled beyond by encompassing the reasonableness doctrine within it. However, the development is still in its rudimentary state in context of Bangladesh as very few cases are dealt with by the Bangladeshi Courts on this issue. As a result, we do not have enough legal premises to make an in-depth analysis of the applicability of the doctrine in our perspective. However, the Grameenphone Ltd vs Chairman case in the First Labor Court has opened a new dimension on this issue through anatomizing an outsourcing contract. It has provoked us to think again of the application of restraint of trade doctrine in employment contracts. But before delving into the matter with a research methodology, we need to know more about it since the texts on the issue of outsourcing are still nascent. The aim of the article is to introduce to the reader the developments of the doctrine of restraint of trade and contextualize it in Bangladesh’s context. Dhaka University Law Journal, Vol. 33(1), 2023 P.49-66